Quasi-guided and photonic modes in 2D macroporous silicon structures with SiO2 nanocoatings - L. Karachevtseva; O. Lytvynenko; K. Parshyn; O. Sapelnikova; Wang Bo (Хімія, фізика та технологія поверхні, 2015)
We investigated the IR light absorption oscillations in 2D macroporous silicon structures with SiO2 nanocoatings 70–800 nm thick. The Wannier–Stark electro-optical effect due to the strong electric field on Si–SiO2 interface and an additional electric field of quasi-guided optical modes were analyzed. The photonic modes and band gaps were also considered as peculiarities in absorbance spectra of macroporous silicon structures with a thick SiO2 nanocoating.